Kemunculan Al-Kitabah di Prodi PAI UIN Ar-Raniry - Huwaida Huwaida (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
Al-Kitabah which is known as one of the maharah (proficiency) in learning Arabic, has become one of the names of courses in the study program. This paper wants to explore the background of the emergence of this course in the PAI program and how the learning process has been going on. To answer the problem the authors conducted a study involving respondents who know directly the process of emergence of this course and student respondents who have followed the learning of this course. The results show that the background of the emergence of al-Kitabah courses is due to efforts to revise the curriculum of the PAI program beginning in 2013. There are various methods applied in al-Kitabah's learning that are adapted to the material which entirely contains the practice of writing Arabic writings. Specifically this course does not require the ability to fabricate in Arabic.